From the functional-brand to the emotional-brand and the consumption experience. An approach to the commodification of experiences in signification advertising. - Vidal Auladell, Felip (2022)
In the transition from a Fordist to a post-Fordist society, the constructive task of the semiotic production of the brand has tilted the functional-brand towards the emotional-brand. For this to occur, as a prerequisite prior to its commodification, a process of rationalization of the emotions described by Illouz has taken place, running parallel to those described by Weber in the sphere of organization of work, and by Adorno in the culture industry. This is exemplified by analyzing the commodification of leisure and tourism through the commercialisation of places.